Network-Scale Impact of Vegetation Loss on Coverage and Exposure for 5G Networks - Jorn Schampheleer; Anke Huss; Margot Deruyck (IEEE Access)
This study investigates the effects of vegetation on 5G network performance, with a particular focus on coverage, user exposure, and base station deployment strategies in an urban environment (Utrecht, The Netherlands). This is the first study to perform network planning simulations that account for vegetation and building-induced propagation challenges on a city-wide scale, providing understanding of their effects on 5G network performance and exposure. The study also explores the influence of user height, examining how vegetation’s blocking and shielding effects vary with user height. By evaluating both sub-6 GHz and mmWave networks under various simulated scenarios, the research qualifies the dual role of vegetation as both a coverage barrier and a mitigator of user exposure. Key findings include a significant 14.71% reduction in coverage for sub-6 GHz networks in the presence of vegetation and a 42.98% decrease in downlink whole-body SAR in mmWave networks due to vegetation’s shielding effects. Flexible base station placement is shown to effectively counteract coverage losses while maintaining stable exposure metrics, but mmWave networks remain highly sensitive to environmental obstructions. These findings emphasize the importance of incorporating vegetation and other environmental factors into network planning, especially for high-frequency 5G networks, to ensure optimal performance and limit user exposure.